Use of hypnotic drugs among Scandinavian children, adolescents, and young adults - R. Wesselhøft; L. Rasmussen; P. Jensen; P. Jennum; S. Skurtveit; I. Hartz; J. Reutfors; P. Damkier; M. Bliddal; A. Pottegård (European Psychiatry, 2022)
Introduction Hypnotic drug use in children and adolescents is widely debated.